Framework of Persistence Layer Synchronous Replication to Improve Data Availability into a Heterogeneous System - Beg, Abul Hashem; Noraziah, Ahmad; Abdalla, Ahmed N.; Rabbi, Khandakar Fazley (IACSIT Press, 2013)
Data replication is an important technique in peer to peer network, data grid architecture, clustering and distributed system, where it increases data availability and enhances data access and reliability and minimizes the cost of data transmission. In this paper, we proposed a framework and structure of synchronous replication from the persistence layer that supports heterogeneous system. In this framework, we developed the multithreading based persistence layer. Our objective is to make the persistence layer more adaptive. In this adaptive persistency system, the replication server will not depend on the main server, so forth, adding a new replication server will be easier than ever, easy to cope with heterogeneous system, cost minimizing and finally there will be no down time.